STUDI KEAMANAN PANGAN PADA TAHU PUTIH YANG BEREDAR DI PASAR SIDOARJO (KAJIAN DARI KANDUNGAN FORMALIN) - Restu Tjiptaningdyah (The East Java Biological Society, 2010)
A lot of substance circulating in the market used preservative as a mean to lengthen a period to keeping. One of them is formalin, its very dangerous poisonous chemicals for health. The aim of this research was to identify the existence of preservative formalin at white tahu in Sidoarjo markets. This was a discriptif research. Sample intake used stratified random sampling method. As basis for stratify is market of place, are traditional and modern market. Identification of formalin content used FMR (formalin mean reagent), with color different as basis criterion. The result showed that 65.90% white tahu circulate in Sidoarjo markets contained the formalin, and 34.10% of white tahu did not contain formalin.